Hiponim Verba Membersihkan dalam Bahasa Jawa - Sutarsih, Sutarsih (Kementerian Sekretariat Negara Republik Indonesia, 2019)
This study discusses the hyponym of the verb cleaning in Javanese language. This hyponym is necessary to study to find the difference and its differentiation to Indonesian language. The data is analized by the component of meaning taken from daily life and dictionary as well as its comparison in Indonesian language; element used, purpose and tool; and the use, based on the existence of the object and passivation. Result of the analysis shows that there are differences between the hyponym of verb cleansing in the Javanese and Indonesian language. The meaning found different in the daily use and in the dictionary; cleaning does not always use water and its element but also use sharp tools or other media depends on its purpose; it does not always need object and could not always be passivied. Those which could be passivied begin with anuswara. Eventhough passivied and grammatically correct, there is a verb that is unlikely being used: ngupil. Keywords: hyponym, verb, cleaning, Javanese language.